Peningkatan Kreativitas Pemecahan Masalah melalui Metode “What’s Another Way” pada Materi Bangun Datar Siswa kelas VII SMP - Warli Warli; Epa Yuliana (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
This study aims to describe the increase in students' creativity in solving mathematical problems and student response after learning the methods of what's another way. To achieve these objectives with the class action research conducted qualitative descriptive approach. Research subjects were students in grade VII SMP N Semanding, Tuban. Data collection techniques, to find out the creativity problem solving is done through task-based interviews. To study the response of students is done through questionnaire responses of students. Analysis of data creativity problem solving creativity refers to the three indicators, namely fluency, flexibility, and novelty. The results showed that subjects with good levels of mathematical ability, moderate and less intelligent, creativity in solving problems increased after the applied method of what's another way. The quality of students' creativity in solving the problem tends to be low. Being the response of students towards learning by using the "what's another way" is very positive.